2021
DOI: 10.1101/2021.05.12.443424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reprogramming adult tendon healing using regenerative neonatal regulatory T cells

Abstract: Tendinopathy is a common clinical problem leading to significant musculoskeletal disability. Using a neonatal mouse model of tendon regeneration compared to adult tendon fibrosis, we identified a unique immune profile in regeneration that is associated with type 2 macrophage polarization and regulatory T cell (Treg) infiltration. Neonatal Treg ablation resulted in a dysregulated immune response leading to failed tenocyte recruitment and loss of functional regeneration. Transcriptional profiling of adult and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Recent work has only begun to appreciate the role of T cells in the tendon 42,43 . Moreover, while a lack of B and T cells did not disrupt tendon development, 5 adoptive transfer of neonatal Tregs into adult hosts improved Achilles tendon functional recovery and polarized macrophages into an anti‐inflammatory profile 44 . Collectively, these data support an important role for T cells in the healing process and merit future work to better define the role of these cells in the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has only begun to appreciate the role of T cells in the tendon 42,43 . Moreover, while a lack of B and T cells did not disrupt tendon development, 5 adoptive transfer of neonatal Tregs into adult hosts improved Achilles tendon functional recovery and polarized macrophages into an anti‐inflammatory profile 44 . Collectively, these data support an important role for T cells in the healing process and merit future work to better define the role of these cells in the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…142 In a recent article about tendon healing, Huang and colleagues marked the persistent collagen damage with CHPs in the transected and unhealed Achilles tendon from neonatal mice with regulatory T cell (Treg) ablation, suggesting that the neonatal Tregs are critical for promoting tendon regeneration. 143 Collagen denaturation has also been implicated in the resolution of organ fibrosis. The hallmark of pulmonary fibrosis, a progressive and devastating interstitial lung disorder, is the excessive deposition of ECM proteins, primarily type I collagen, by activated fibroblasts.…”
Section: Collagen Denaturationmentioning
confidence: 99%
“…The Molkentin group showed that intracardiac injection of stem cells induces the accumulation of CX3CR1 + and CCR2 + macrophages in the active remodeling region of the heart (Figure c), which can reduce fibrosis and enhance the mechanical properties of the injured area by regulating the activity of local fibroblasts . In a recent article about tendon healing, Huang and colleagues marked the persistent collagen damage with CHPs in the transected and unhealed Achilles tendon from neonatal mice with regulatory T cell (Treg) ablation, suggesting that the neonatal Tregs are critical for promoting tendon regeneration …”
Section: Biology Of Collagen Hybridizationmentioning
confidence: 99%
“…Recent work has only begun to appreciate the role of T cells in tendon (42,43). Moreover, while a lack of B and T cells did not disrupt tendon development (5), adoptive transfer of neonatal Tregs into adult hosts improved Achilles tendon functional recovery and polarized macrophages into an anti-inflammatory profile (44). Collectively, these data support an important role for T cells in the healing process, and merit future work to better define the role of these cells in the healing process.…”
Section: Discussionmentioning
confidence: 99%